Chasing the last laugh : Mark Twain's raucous and redemptive round-the-world comedy tour - Zacks, Richard (Doubleday, 2016)
"From Richard Zacks, bestselling author of The Pirate Hunter and Island of Vice, a rich and lively account of Mark Twain's late-life adventures abroad In 1895, at age sixty, Mark Twain was dead broke and miserable--his recent novels had been critical and commercial failures, and he was bankrupted by his inexplicable decision to run a publishing company. His wife made him promise to pay every debt back in full, so Twain embarked on an around-the-world comedy lecture tour that would take him from the dusty small towns of the American West to the faraway lands of India, South Africa, Australia, and beyond. Richard Zacks' rich and entertaining narrative provides a portrait of Twain as complicated, vibrant individual, and showcases the biting wit and skeptical observation that made him one of the greatest of all American writers. Twain remained abroad for five years, a time of struggle and wild experiences -- and ultimately redemption, as he rediscovered his voice as a writer and humorist, and returned, wiser and celebrated. As he said in his famous reply to an article about his demise, "the report of my death is an exaggeration." Weaving together a trove of sources, including newspaper accounts, correspondence, and unpublished material from Berkeley's ongoing Twain Project, Zacks chronicles a chapter of Twain's life as complex as the author himself, full of foolishness and bad choices, but also humor, self-discovery, and triumph"--